Pengaruh Investment Opportunity Set (IOS) Kebijakan Deviden dan Keputusan Pendanaan Terhadap Nilai Perusahaan - Raihan Nawalia Alayidrus; Meta Nursita (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the effect of investment opportunity set (ios), dividend policy, and funding decisions on firm value. The object of research is companies in the property & real estate sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The sampling technique used was purposive sampling method, with a total sample of 9 companies for 5 years of observation, so that 45 observations were obtained. The data used is sukender with quantitative data sourced from annual financial reports. Data analysis was carried out using the panel data regression method with the help of EViews 12 software. The results showed that simultaneously, investment opportunity set (IOS) dividend policy, and funding decisions have a significant effect on firm value. Partially, investment opportunity set (IOS) has a positive and significant effect on firm value. Dividend policy has a positive and significant effect on firm value, and funding decisions have a positive and significant effect on firm value.